E-MODUL SEBAGAI SARANA PEMBELAJARAN JARAK JAUH (PJJ) DI ERA PANDEMI COVID-19 - Sulistyorini, Wahyu (FKIP Unirow Tuban, 2022)
This Best Practice aims to find out how to use electronic modules (e-modules) in Biology class XI MIPA SMA Negeri 2 Tuban material about Structure and Function of Cells in the Covid-19 pandemic era. The method used in solving this problem is the method of interviewing one group in a certain period of time by using one intervention, namely the use of electronic modules (E-modules) on the structure and function of cells. The results of online interviews using the Teams application with students on average there were positive responses, very happy and with the E-module because the focus was on learning one Basic Competency (KD), lots of color pictures so it was more interesting and also very clear pictures as well as the explanation, as well as the practice questions which are accompanied by answer keys so that they are easy to understand and students can explain critical thinking learning activities for example given pictures of cell organelles students can describe the structure of the existing images and explain their functions, from assignments existing students also more easily understand the concept of cell structure and function. Students' way of thinking also changes, students not only memorize the material but understand the material better. , although there are still some yan g is still below the KKM. Things that need to be fixed, students haven't opened the module, because at that time what was sent was a link, it's possible it couldn't be opened because of several obstacles including the package running out, the signal was disrupted or there was no internet at home. Seeing these conditions, educators change sending files so that they are easy to open and study. This e-module can be opened anytime and anywhere. The use of this E-module is very effective during a pandemic like today, understanding concepts is easier, critical thinking skills are also emphasized, so it can be concluded that E-modules can improve students' critical thinking skills and get positive responses from students.